2012
DOI: 10.1002/asi.22607
|View full text |Cite
|
Sign up to set email alerts
|

Alternative thoughts on uncitedness

Abstract: In a recent article, L. Egghe, R. Guns, and R. Rousseau (2011) noted that in a study of some eminent scientists, many of them had a fair proportion of papers which were uncited and found this to be surprising. Here, we use the stochastic publication/citation model of Q.L. Burrell (2007) to show that the result might in fact be expected. This brief communication is in the spirit of Q.L. Burrell (2002, 2005), showing that results that might at first sight seem to be surprising can in fact often be explainable in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Of the papers included in WoS, 13.5 ± 6.2% of those (co)authored by Fields medalists and 13.7 ± 6.6% of those (co)authored by Nobel Prize laureates were uncited. Because the search corroborated the previously published results (Egghe et al., ), in agreement with the stochastic publication/citation model suggested by Burrell (, ), I next focused on the variables with the potential to influence the observed ratio.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Of the papers included in WoS, 13.5 ± 6.2% of those (co)authored by Fields medalists and 13.7 ± 6.6% of those (co)authored by Nobel Prize laureates were uncited. Because the search corroborated the previously published results (Egghe et al., ), in agreement with the stochastic publication/citation model suggested by Burrell (, ), I next focused on the variables with the potential to influence the observed ratio.…”
Section: Resultssupporting
confidence: 69%
“…Although this is an interesting hypothesis, and although the more recent authors suggested even two models explaining the pattern of uncitedness [Lotkaian model by Egghe et al. (), and stochastic model by Burrell ()], none of the above researchers verified the characteristics of papers being uncited. Egghe et al.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Continuing their long association with so‐called Lotkaian informetrics, in Egghe and Rousseau ) they assume a continuous (approximate) form for the distribution of citations over productive sources which, in the standard size‐frequency form is written f 1 ( j ) = C 1 j α 1 , j 1 where α > 2 is referred to as the Lotka index. To compensate for the criticism of this model that it makes no mention of the uncited sources (see, e.g., Egghe, Guns, & Rousseau, , and Burrell, ), in Egghe and Rousseau (, ) we find the so‐called shifted Lotka function with size‐frequency form f 0 ( j ) = C 0 ( j + 1 ) α 0 , j 0 Remark Strictly speaking, (1) gives Lotka's law in the case where j takes positive integer values. For the continuous case (1) is the standard (Type I) Pareto distribution, after Pareto (, , ,).…”
Section: Introductionmentioning
confidence: 94%
“…() revealed that the former tend to be “late heartbeats” (most citations were received in the second half of the sleeping period), whereas the latter tend to exhibit “early heartbeats” (most citations were received in the first half of a sleeping period). In addition, the number of never cited publications (“uncitedness”) is large, even if the authors are Nobel Laureates (Burrell, ; Egghe, Guns, & Rousseau, ; Heneberg, ). The citation boost required in the new criteria does not necessarily “abruptly” attract a lot of attention, as indicated by van Raan ().…”
Section: Discussionmentioning
confidence: 99%